Conversor CC/CC de alto ganho sem capacitor eletrolítico aplicado a um sistema fotovoltaico - Freitas, Antônio Alisson Alencar (2012)
The photovoltaic sector has been distinguishing itself from all other renewable energy sources, due to its large growth through the last years. For this reason, it has become the third major clean source of power generation worldwide. In Brazil, this sector still doesn’t have great pertinence in the energy matrix, given the imported technology of converters and panels. Considering the demand to develop this technology, this paper propounds the research and implementation of a high gain DC/ DC converter applied to photovoltaic systems, which aims mainly to remove energy from a photovoltaic module and inject it into a DC constant bus. A photovoltaic module is connected to the input of the high gain converter, with an output voltage equals to 17 Vdc. This converter raises its input voltage and injects its output current at a constant 311 Vdc bus, using the maximum power point tracking (MPPT). The laboratory implemented prototype was designed for a rated power of 100W and it doesn’t have electrolytic capacitors, thereby increasing the lifetime of the converter and also allowing the incorporation the converter to the photovoltaic module. The prototype had a strong and low cost performance, necessary characteristics for a converter applied to renewable energy sources. The prototype performance exceeded the author’s expectations, in relation to the maximum power point tracking. Thus, a quite simple algorithm can be extremely reliable when choosing to configure a converter through a module.